ChemInform Abstract: Asymmetric Organocatalytic Cascade Michael/Hemiketalization/Retro‐Aldol Reaction of 2‐[(E)‐2‐Nitrovinyl]phenols with 2, 4‐Dioxo‐4‐arylbutanoates: A Convenient Access to Chiral α‐Keto Esters. Issue 14 (8th April 2014) - Liu, Yunting; Wang, Youming; Song, Haibin; Zhou, Zhenghong; Tang, Chuchi
Abstract The title reaction is optimized using a bifunctional tertiary amine‐squaramide as catalyst.